2000
DOI: 10.1097/00003072-200010000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Malignant Lymphomas with F-18 FDG Coincidence Detection Positron Emission Tomography

Abstract: Conclusions: For staging, FDG CoDe PET alone without attenuation correction is not sensitive enough to be used as an independent imaging method, especially for small abdominal lesions. However, it appears to be an accurate method for assessing residual disease and for patient follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2001
2001
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
0
3
0
2
Order By: Relevance
“…(2) and (3), lymphoma [8,11], and melanoma [12,13]. FDG can also be used for staging and restaging and for therapeutic monitoring of breast cancer [14,15].…”
Section: / Fluorodeoxyglucose (Fdg) and The Glycolytic Metabolic Patmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) and (3), lymphoma [8,11], and melanoma [12,13]. FDG can also be used for staging and restaging and for therapeutic monitoring of breast cancer [14,15].…”
Section: / Fluorodeoxyglucose (Fdg) and The Glycolytic Metabolic Patmentioning
confidence: 99%
“…11 C-labelled methionine was then used to delineate tumour tissue. The exact mechanism of tumour uptake has not been elucidated and several studies have demonstrated the lack of specificity of 11 C-methionine for protein synthesis [45] and only showed that 11 C-methionine had a high affinity for tumours [46]. Some studies demonstrated that 11 C-methionine uptake was correlated with proliferation markers in patients with brain and lung carcinoma [47][48][49], but other studies failed to find any correlation in patients with head and neck and lung carcinoma [50,51].…”
Section: / Amino Acid Transport and Metabolismmentioning
confidence: 99%
“…7 Woolfenden et al developed and tested a mini-NaI͑Tl͒ probe that was passed through the channel of a bronchoscope to detect gamma arrays emitted by 57 Co-labeled-bleomycin preferentially absorbed in lung cancers. 8 Discovery of the excellent targeting of FDG to many cancers [9][10][11][12][13][14][15][16] has led to the proposed application of positronsensitive probes to guide surgeries. A significant complication incurred by the use of positron emitters for surgical guidance is the creation of 511 keV annihilation photons.…”
Section: Introductionmentioning
confidence: 99%
“…Células escamosas epiteliais e ninhos ou ilhas de células são observadas crescendo como entidades independentes dentro do tecido conjuntivo, muitas vezes sem ligação com o epitélio de superfície. As células da lesão podem destruir os vasos sangüíneos, e invadir o lúmen de veias ou vasos linfáticos (MAJNO;JORIS, 1996;NEVILLE et al, 2004 (HEMINGWAY et al, 1996;LIMA, 2002): utilizando um substrato com características ideais que incluem uma biodistribuição adequada para atingir o objetivo (o tecido alvo), com ausência de toxicidade ou efeitos secundários, é possível identificar e mapear a alteração presente em todo o corpo humano (BRAAMS et al, 1996;LIMA, 2002); o substrato de eleição 18 F-FDG da presente pesquisa tem uma alta captação em neoplasias malignas, segundo estudos in vitro, e esta captação está relacionada à avidez das células tumorais por este substrato, o que é proporcional à sua atividade metabólica (HANNAH, 2002); o tempo de meia-vida deste substrato (109 minutos) tem um papel decisivo em sua escolha, pois é suficiente para a realização do exame PET-CT sem que haja perda das informações necessárias, já que decorrido o período de meia-vida restará apenas cerca de 50% da radioatividade originalmente presente (CONTI;LILIENI;HAWLEY, 1996;GAMBHIR et al, 2001;KIM, 2000).…”
Section: Introductionunclassified
“…Quanto aos diferentes equipamentos existentes, podemos destacar a gama câmara com colimadores de alta energia, utilizadas na detecção de fótons de 511 keV (BEYER et al, 2004;BOCHER et al, 2001;VOGEL et al, 2004). Este aparelho detector de dupla coincidência tem algumas limitações, como imagens de baixa resolução, com uma qualidade inferior em comparação à obtida em aparelho PET dedicado (SHREVE et al, 1998), mesmo assim, pode ser uma razoável alternativa, como bem demonstrado na literatura (AK et al, 2001;HWANG et al, 2000).…”
Section: Introductionunclassified